2004
DOI: 10.1086/422397
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mannose‐Binding Lectin in the Innate Defense againstCandida albicans:Enhancement of Complement Activation, but Lack of Opsonic Function, in Phagocytosis by Human Dendritic Cells

Abstract: Mannose-binding lectin (MBL) is a serum collectin believed to be of importance in innate immunity. We have investigated the role of MBL in the first-line defense against Candida albicans, an opportunistic fungal pathogen. MBL bound C. albicans via its lectin domain, resulting in agglutination of the organisms upon their outgrowth of hyphae. In a human in vitro MBL system, deposition of C4 fragments on C. albicans was increased when exogenous MBL was added to serum samples from MBL-deficient individuals. Simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 60 publications
0
72
1
4
Order By: Relevance
“…27) Neth et al analyzed the concentration of MBL in various inbred strains and found that all of the strains tested contained MBL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27) Neth et al analyzed the concentration of MBL in various inbred strains and found that all of the strains tested contained MBL.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports indicated that Candida albicans could bind to MBL. 27,28) We have shown that CAWS-induced arteritis and anaphylactoid reaction is dependent on strains of mice. In the present study, we demonstrated the essential structure to induce arteritis and anaphylactoid reaction.…”
Section: Discussionmentioning
confidence: 99%
“…MBL binds mannans in the cell walls of C. albicans both in vitro and in vivo [24], leading to complement deposition via the lectin pathway and subsequent phagocytosis [24,25]. In contrast, MBL binding to Blastomyces dermatitidis masks 1,3-beta-glucan recognition by macrophages, hindering the secretion of TNF-α [26].…”
Section: Phagocytosismentioning
confidence: 99%
“…MBL has been shown to bind to Candida albicans augmenting complement activation (14) and facilitating phagocytosis (15) (20,21), data are lacking with regard to Candida infections.…”
Section: Introductionmentioning
confidence: 99%